(untitled) (Ameghiniana, 2013)
The present paper deaIs with the study of the microplankton of the Río Turbio Formation (Eocene), outcropping in the SW of Santa Cruz Province. In the first part, some previous geological considerations are mentioned and discussed; they show many divergencies of opinion. The lithostratigraphic units, as proposed by Hunicken in 1955 are accepted, having priority and being correctly formulated, following the use of the Stratigraphic Codeo Brief mentions are made about the previous palynologicaI investigations which bear some re1ation to the area here studied. In the second part, the description of 16 taxa is presented, the following being new: Deflandrea ectorugosa, D. endopapillata, Hystricbospbaera membranosa, Cleistosphaeridium patagonicum and Adnatosphaeridium hunickenii. Comments on some previously described taxa are aIso made, especially Turbiosphaera [ilosa of which different kinds of cyst development have been found. In the last part, the distribution of all studied species in the Turbio Formation is considered. A table, indicating frequency and range of 27 species is presented; further, the frequency and range of the 7 most important species is presentad in a more detailed table. Two different associations have been found: Association A composed by Turbiosphaera filosa, Spinidinium rotundum, Deflandrea macmurdoensis and Cleistospbaeridium bergmanii; Association B with Cordospbaeridium dictyoplokus, Spinidinium rotundum, Thalassiphora pelágica and Deflandrea granulata. There are 8 species which are common to both associations; it is believed that there is no important time gap between both associations. Further, comparisons of Associations A and B with other associations from Argentina, neighbouring, gondwanic and extragondwanie areas are made. It is suggested that the Río Turbio Formation is partly synchronous with the Chilean Leña Dura and Loreto Formation from the Magallanian district. A close agreement with the Me Murdo Sound Associations in Antaretica is also evident. On the base of the stratigraphieaI range of known species found in different areas, it is eoncluded that the Río Turbio Formation, more than 500 meters thick, ranges from the top of the Lower Eocene up to the base of the Upper Eocene. Thus, the Oligocene age for part of this column, suggested by previous authors, is not aecepted.